The weathermonger - Dickinson, Peter (Delacorte Press, 1986)
People of the future recreate the Middle Ages by destroying Machines and by subjecting anyone found with a machine or a knowledge of mechanics to severe punishment or death.
People of the future recreate the Middle Ages by destroying Machines and by subjecting anyone found with a machine or a knowledge of mechanics to severe punishment or death.
Keywords: Science fiction. / http://id.loc.gov/authorities/subjects/sh85118629